Factors of Students’ Motivation in Enrolling the Department of Arabic Language, Kulliyyah of Languages and Management - Mohammad Izani, Izyan Nazurah; Mohd Ismath, Nurul Hanilah (Kulliyyah of Languages & Management(KLM), International Islamic UniversityMalaysia, Edu Hub Pagoh, 84600 Muar, Johor Darul Takzim., 2022)
The process of learning a second or third language is not easy for non-native students to master it. Motivation plays an important role and has a significant impact in the field of education and learning as it makes the process more effective. This study aims to seek students' attitudes towards learning Arabic and emphasize the motivation of students enrolling in the Arabic Language Department, Kulliyyah of Languages and Management adopted the descriptive analytical method. The researcher selected 100 students from the first and second years in the second semester of the academic year 2022/2021 as a research sample and distributing the questionnaire to them via the Google Form link. The result showed including: (1) The research sample have positive trends towards Arabic because they discover that Arabic is a useful language to learn. (2) The factors that motivated students to learn Arabic because of their interest in learning Arabic. This is one of the internal factors driving and orienting their behavior towards learning and achieving their educational goals. The researcher then concluded her study with recommendations and suggestions.